Crueldade e melancolia em O morro dos ventos uivantes, de Emily Brontë - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The book Wuthering Heights (1847), by the English novelist Emily Brontë brings philosophical biases the theme of cruelty and melancholy, both of them, presented inside of a uncommon place with self-destructive characters whose psychological profile moves the plot. Besides, the philosophical tone raised the themes, the gothic nature of the book were the items that guided the interest in investigating the procedures adopted in the language and the novelistic techniques highlighted in it, since the author crumbles literary canons established, due to the high degree of experimentation with the language – the speech in Wuthering Heights is a clear marker of superiority and inferiority – the use of multiple narrators and also a protagonist with chances of being a bastard son with a gypsy origin who falls in love with a woman that belongs to the English middle class. All these aspects were quite inappropriate for a woman’s pen. Notably Brontë’s book corrupted the puritan values and it provoked a rebuke immediate from the nineteenth-century society. This research is based on the theories of Tzvetan Todorov about the fantastic narrative due to the Gothic nature of the book, in Clément Rosset by his literary studies present in The Principle of Cruelty, in Black Sun: Depression and Melancholy by Julia Kristeva and others.
Keywords: O morro dos ventos uivantes; Crueldade; Melancolia; Emily Bronte; LINGUÍSTICA, LETRAS E ARTES: LETRAS